Financing Sustainable Landscapes through Innovative International Economic Law and Governance Instruments - Cordonnier-Segger, M.-C.; Holmgren, P.; Wardell, D.A. (Brill, 2018)
This article examines innovative ways to promote investment and financing of sustainable landscape initiatives in international law. It argues that increased flows of investment and finance for sustainable landscapes must be guided by a clear and comprehensive legal framework; better and more appropriate knowledge and technologies; more informed decision-making; and improved governance at all levels.The article considers concerns and opportunities to support the financing of sustainable forestry and land-use programs, especially in developing countries. It reviews the key contributions of international investment instruments to sustainability landscapes financing, in light of recent decisions concerning International Investment Agreements (iias) by arbitral panels convened to hear disputes under the rules of the International Centre for Settlement of Investment Disputes (icsid) or the United Nations Commission on International Trade Law (uncitral). It then proposes innovative ways that investment and financing rules might foster more effective implementation of innovative financing instruments, such as Landscape Funds in developing countries.